2016
DOI: 10.1371/journal.pone.0164640
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of FGF5 in Cashmere Goats Using CRISPR/Cas9 Results in More Secondary Hair Follicles and Longer Fibers

Abstract: Precision genetic engineering accelerates the genetic improvement of livestock for agriculture and biomedicine. We have recently reported our success in producing gene-modified goats using the CRISPR/Cas9 system through microinjection of Cas9 mRNA and sgRNAs targeting the MSTN and FGF5 genes in goat embryos. By investigating the influence of gene modification on the phenotypes of Cas9-mediated goats, we herein demonstrate that the utility of this approach involving the disruption of FGF5 results in increased n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 22 publications
1
56
0
1
Order By: Relevance
“…Hematoxylin and eosin (H&E) staining indicated more secondary hair follicles in the skin of BE3 edited goats (Figs B and ). Considering our previous report , these results confirmed that inducing point mutations through BE3 yielded a similar phenotype to site‐directed nuclease gene disruption by DSB and repair.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Hematoxylin and eosin (H&E) staining indicated more secondary hair follicles in the skin of BE3 edited goats (Figs B and ). Considering our previous report , these results confirmed that inducing point mutations through BE3 yielded a similar phenotype to site‐directed nuclease gene disruption by DSB and repair.…”
Section: Resultssupporting
confidence: 86%
“…The encoded protein of FGF5 is secreted during the hair growth cycle to signal inhibition of hair growth by a mechanism that blocks dermal papilla cell activation [19]. FGF5 is regarded as the causative gene responsible for the angora phenotype (long hair) in mice [20], and we have previously shown that disruption of FGF5 via CRISPR/Cas9 resulted in longer hair fibers and a 30% increase in cashmere yield per animal [21,22]. In the present study, we demonstrated that the BE3 system can achieve high efficiency single base substitution in FGF5, when introduced by microinjection into single-cell embryos.…”
Section: Introductionmentioning
confidence: 99%
“…; Wang et al . ). FGF5 was up‐regulated in the L group, indicating that FGF5 expression has a positive effect on wool growth.…”
Section: Resultsmentioning
confidence: 97%
“…; Wang et al . ). The sequencing data from the F1 animal (#9_F1) further confirmed the high fidelity of germline transmission from edited animals (Fig.…”
Section: Discussionmentioning
confidence: 97%